Sleep the myth of 8 hours, the power of naps ... and the new plan to recharge your body and mind - Littlehales, Nick (Da Capo Lifelong, 2018)
"One-third of our lives--that's 3,000 hours a year--is spent trying to sleep. The time we spend in bed shapes our moods, motivation, alertness, decision-making skills, reaction time, creativity ... in short, our ability to perform, whether at work, at home, or at play. But most of us have disturbed, restless nights, relying on over-stimulation from caffeine and sugar to drag us through the day. The old eight-hour rule just doesn't work, and it's time for a new approach. Endorsed by leading professionals in sports and business, Sleep shares a new program to be your personal best. Nick Littlehales is the leading sport sleep coach to some of the biggest names in the sporting world, including record-breaking cyclists for British Cycling and Team Sky, international soccer teams, NBA and NFL players, and Olympic and Paralympic athletes. Here, he shares his proven strategies for anyone to use. You'll learn how to map your unique sleep cycle, optimize your environment for recovery, and cope with the demands of this fast-paced, tech-driven world. Read Sleep and rest your way to a more confident, successful, and happier you."--Back cover.